HUBUNGAN ANTARA BEBAN KERJA DENGAN KELELAHAN KERJA KARYAWAN LAUNDRY DI KELURAHAN WARUNGBOTO KECAMATAN UMBULHARJO KOTA YOGYAKARTA - MZ, Murleni Wati; Hariyono, Widodo (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: A problem which related with ergonomy factor commonly caused by conformity between the worker with occupation circles completely include occupation tools and the energy need or the amount of calori which used by the worker. Light in weight occupation which must be done by a worker will depend on changes indication appear and can be measured by measuring human part of body such as the rapid artery beat. The kind of measuring done for knowing how big the physical load accepted by the worker so that cause weariness. This experiment as a purpose to know the relation between the occupation weariness of the laundry workers in Kelurahan Warungboto Kecamatan Umbulharjo Yogyakarta City.Method: The kind of this experiment is observational analytic with study program Cross Sectional. The data interpretation done by measuring of artery beat on wrist (radical artery) to see the respondent occupation load and measuring weariness by Reaction timer tool.Result: From the test result statistic, so respondent there are relation between occupation load with occupation weariness Laundry worker in Kelurahan Warungboto Kecamatan Umbulharjo Yogyakarta city statistically mean (Sig-2 tailed 0,0000). Ho which states is no relationship between load with occupation weariness of the laundry worker rejected Ha which states there is relationship between load with occupation weariness of the laundry worker accepted.Conclusion: There are relation that mean between occupation load with occupation weariness of the laundry worker in Kelurahan Warungboto Kecamatan Umbulharjo Yogyakarta city.Keyword: Occupation load, Artery beat, Occupation weariness and Reaction timer.